THE IMPACT ANALYSIS OF THE EU-KOREA FTA ON THE CZECH SENSITIVE SECTORS WITH SPECIAL ATTENTION TO THE AUTOMOTIVE INDUSTRY - Baladová, Šárka; Urban, Luděk, 1927-2013; Munzi, Tomáš, 1980-; Vysoká škola ekonomická v Praze. Národohospodářská fakulta (2010)
Strong objections appeared in the Czech Republic, especially in the automotive industry, against the EU-Korea Free Tra de Agreement right after its adoption in October 2009. There were fears that the Agreement would endanger Czech competitiveness in the European market while new opportunity for Czech exporters in the Korean market would be limited. The thesis aims to analyze the impacts of the Agreement on the Czech sensitive sectors as the author does not agree with the results of the very first Czech country specific analysis made by the Association for International Affairs (AMO) that neglects any important endangering effects of the Agreement. The crucial difference between this paper and the study made by AMO is that the author considers Czech competitiveness in the European market as a decisive criterion while AMO analysts analyze the impacts on the Czech market only. They do not consider Czech exports to the EU member states and potentially strengthening competition in the European market for Czech producers. In the thesis the sensitive sectors are defined using the data from the International Trade Centre (ITC), the Czech statistical office, and the UN COMTRADE. Hariss index is used to measure restrictiveness of the rules of origin for the very first time in the EU-Korean FTA context, the methodology of the European Commission is utilized to estimate potential savings in effect of duty drawback, and a qualitative analysis of the non-tariff barriers is applied. The author points at a decisive function of non tariff barriers that plays even more important role in terms of liberalization then tariff reduction itself. Regarding the automotive industry, the thesis shows that Czech competitiveness within heading 8703 (cars) will not be endangered in effect of the Agreement while there might be some difficulties within heading 8708 (parts & accessories for motor vehicles).
The Czech Republic does not perform any revealed competitive advantage in trade of services. The arguments of Czech car makers against the Agreement about the trade within heading 8703 are not admitted. However further research is needed to analyze if the Agreement will have harmful effects on Czech competitiveness in the European market within heading 8708. The Agreement will not bring up any notable opportunity for Czech exporters in the Korean market.
Vedoucí práce: Luděk Urban
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Způsob přístupu: Internet
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Národohospodářská fakulta, 2011
Rok obhajoby 2011
Keywords: hospodářská politika [obor dipl. práce]; diplomové práce; master's theses